CEO DUALITY, AUDIT TENURE, FIRM COMPLEXITY, AND FINANCIAL REPORTING INTEGRITY: THE MODERATING EFFECT OF FIRM RISK - Chantika Nurfitriani; Imas Kismanah (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study investigates what factors influence financial statement integrity within the property and real estate sector. This particular sector carries two distinctive characteristics: operational complexity and high financial pressure. Prior research examining CEO duality, audit tenure, and firm complexity has yielded inconsistent findings across different studies. Furthermore, the moderating role of firm risk in these relationships remains largely underexplored. These conditions point to a clear research gap. The present study analyzes how governance attributes influence financial statement integrity. It also examines whether firm risk moderates these relationships. Secondary data from the 2020 to 2024 period provides the empirical foundation. Panel regression combined with a moderated regression analysis approach serves as the analytical technique. Several findings emerge from the results. Audit tenure shows a significant negative effect on financial statement integrity. CEO duality and firm complexity demonstrate no significant impact. Firm risk significantly moderates the effects of audit tenure and firm complexity. However, firm risk does not moderate the CEO duality relationship. The study concludes that auditor independence and firm risk levels occupy an essential role in determining financial reporting quality.